Fire and disaster detection with multimodal quadcopter By machine learning - Afrin, Anika; Rahman, Md Moshiour; Chowdhury, Ayash Hossain; Eshraq, Mirza; Ukasha, Mehvish Rahman (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.